KARAKTERISASI KEJU DANGKE MENGGUNAKAN ENZIM PAPAIN KOMERSIAL DAN PERUBAHAN FISIK SELAMA PENYIMPANAN - Nurul Ilmi Musra; Sedarnawati Yasni; Elvira Syamsir (Jurnal Teknologi dan Industri Pangan, 2021)
Dangke is one of the traditional cheeses made from buffalo milk or cow's milk from Enrekang, South Sulawesi,. This research aimed to obtain dangke cheese through a process using commercial papain as the curdling agent and to determine the best products based on the analysis of physical properties of the raw materials and the dangke. The dangke making was conducted using several concentrations of the commercial papain (0.2-5%). Based on the texture, yield and non-bitter taste intensity, the best dangke was obtained using 1, 3, and 5% commercial papain. Dangke made using 1, 3, and 5% commercial papain resulted in yields of 18, 17, and 18%, respectively with compact texture and non-bitter taste. At room temperature storage (±30°C), the dangke had shelf life of less than 24 hours, while at low temperature storage (±4°C), dangke could last for four days.